MONITORING TRAINING LOADS, STRESS, IMMUNE-ENDOCRINE RESPONSES AND PERFORMANCE IN TENNIS PLAYERS - Rodrigo Vitasovic Gomes; Alexandre Moreira; Leandro odo; Ken Nosaka; Aaron James Coutts; Marcelo Saldanha Aoki (Termedia Publishing House, 2013)
The study aim was to investigate the effect of a periodised pre-season training plan on internal training load and subsequent stress tolerance, immune-endocrine responses and physical performance in tennis players. Well-trained young tennis players (n = 10) were monitored across the pre-season period, which was divided into 4 weeks of progressive overloading training and a 1-week tapering period. Weekly measures of internal training load, training monotony and stress tolerance (sources and symptoms of stress) were taken, along with salivary testosterone, cortisol and immunoglobulin A. One repetition maximum strength, running endurance, jump height and agility were assessed before and after training. The periodised training plan led to significant weekly changes in training loads (i.e. increasing in weeks 3 and 4, decreasing in week 5) and post-training improvements in strength, endurance and agility (P < 0.05). Cortisol concentration and the symptoms of stress also increased in weeks 3 and/or 4, before returning to baseline in week 5 (P < 0.05). Conversely, the testosterone to cortisol ratio decreased in weeks 3 and 4, before returning to baseline in week 5 (P < 0.05). In conclusion, the training plan evoked adaptive changes in stress tolerance and hormonal responses, which may have mediated the improvements in physical performance.